2021
DOI: 10.3390/ijerph18094677
|View full text |Cite
|
Sign up to set email alerts
|

Land Tenure and Green Production Behavior: Empirical Analysis Based on Fertilizer Use by Cotton Farmers in China

Abstract: Stable land rights can increase farmers’ expectations regarding the future and encourage their adoption of green production methods, which is an important guarantee for promoting the development of green agriculture development. This paper takes the fertilizer use as an example and systematically investigated the impact of land tenure stability on the green production behavior of heterogeneous farmers based on a field survey data of 349 cotton-planting farmers from Xinjiang, China. Furthermore, this research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…These findings provide a valuable reference for this paper. Based on the empirical analysis of the micro-data of Sichuan Province in China, this paper finds that land inflow (LRI) significantly increases the level of green agricultural production (GPA), which supports the views and conclusions of Sun et al [3], Hui and Yu [22]. The contributions of this paper include: (1) using micro data sets from China, we explore the impact of land transfer on green agricultural production, and the results verify the reliability of some existing literature conclusions, (2) this paper not only analyzes the impact of land transfer on agricultural green production but also discusses the heterogeneity of farmers, furthermore, the moderating effect of agricultural training, digital literacy and agricultural loan on the impact of land transfer on green agricultural production is analyzed, which makes the research results more comprehensive and clear, and less in the existing literature However, this paper also has some limitations: (1) using the data of Sichuan Province in China, the conclusions may be more applicable to China (region).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings provide a valuable reference for this paper. Based on the empirical analysis of the micro-data of Sichuan Province in China, this paper finds that land inflow (LRI) significantly increases the level of green agricultural production (GPA), which supports the views and conclusions of Sun et al [3], Hui and Yu [22]. The contributions of this paper include: (1) using micro data sets from China, we explore the impact of land transfer on green agricultural production, and the results verify the reliability of some existing literature conclusions, (2) this paper not only analyzes the impact of land transfer on agricultural green production but also discusses the heterogeneity of farmers, furthermore, the moderating effect of agricultural training, digital literacy and agricultural loan on the impact of land transfer on green agricultural production is analyzed, which makes the research results more comprehensive and clear, and less in the existing literature However, this paper also has some limitations: (1) using the data of Sichuan Province in China, the conclusions may be more applicable to China (region).…”
Section: Discussionsupporting
confidence: 80%
“…This kind of income also brings more investment space to farmers, which further urges them to produce in a green way. Second, a stable land ownership relationship can reduce the loss of agricultural investment, thereby increasing the expected income of farmers, driving farmers to expand their long-term investment, and stimulating farmers to adopt green production technologies, especially for farmers with relatively large production scale [22]. At the same time, green agricultural technology will also bring trans period benefits to farmers [23].…”
Section: Introductionmentioning
confidence: 99%
“…The non-farm employment of rural labor force is closely related to the rural land system [ 7 ], as the adjustment of contracted land management rights will reduce farmers’ expectation of the stability of land rights [ 8 , 9 ], make farmers divest their possession of land use rights and turn to invest more labor force in the field of non-farm production [ 10 , 11 , 12 ]. Subsequently, many scholars found that land right confirmation can increase the expectation of pure farming farmers on the stability of land property rights and eliminate their concerns after land transfer [ 13 , 14 , 15 ]; moreover, the land scale effect will improve agricultural production efficiency [ 16 ], thus promoting the employment of rural labor force [ 17 ]. However, some scholars have found that land right confirmation can enhance farmers’ right to dispose of land, improve the comparative advantage of agricultural production by reconfiguring agricultural production factors and improve farmers’ expectation of future agricultural income and enthusiasm for agricultural production [ 18 ], thus increasing the investment in land, indirectly increasing the opportunity cost of non-agricultural employment and restraining the willingness of land transfer and non-agricultural employment.…”
Section: Literature Review and Theoretical Mechanismsmentioning
confidence: 99%
“…Researches on the green production transformation of small farmers mainly focus on the influencing factors of the green production behavior of small farmers. Mao et al (2021) explored the impact of land ownership on farmers' green production behavior. Through regression analysis, (Li et al, 2021b) found that farmers' age, land type, land transfer compensation, technical service institutions, training, and subsidies have a significant impact on their willingness to produce green agriculture.…”
Section: Introductionmentioning
confidence: 99%